Cockroach wings-promoted safe and greener synthesis of silver nanoparticles and their insecticidal activity - Khatami, Mehrdad; Iravani, Siavash; Varma, Rajender S; Mosazade, Farideh; Darroudi, Majid; Borhani, Fariba (Bioprocess and biosystems engineering, 2019)
Simpler and biocompatible greener approaches for the assembly of nanoparticles (NPs) have been the focus lately which have minimum environmental damage and often entails the use of natural biomolecules to synthesize NPs. Such greener synthesis of nanoparticles has capitalized on the use of microbes, fungi, and plants using biological resources. In this study, Periplaneta americana (American cockroach) wings' extract (chitin-rich) is studied as a novel biomaterial for the first time to synthesize silver NPs (less than 50 nm); chitin is the second most abundant polymer after cellulose on earth. The physicochemical properties of these NPs were analyzed using UV-visible spectroscopy, X-ray diffraction, and transmission electron microscopy (TEM). The insecticidal effect of ensuing NPs was examined on the mortality of Aphis gossypii under laboratory conditions; 48 h after treatments of A. gossypii with silver NPs (100 μg/ml), the mortality rate in treated aphids was about 40% (an average), while an average percentage of losses in the control sample was about 10%. These results indicate the lethal effect of green-synthesized silver NPs on A. gossypii, in vitro. Greener synthesis of silver nanoparticles using American cockroach wings and their insecticidal activities.
Keywords: celulosa; technologie zelené chemie; Periplaneta; Wings, Animal; Green synthesis; Natural biomolecules; Silver; Insecticidal activity; difrakce rentgenového záření; Green Chemistry Technology; chitin; křídla zvířecí; insekticidy; průmyslová mikrobiologie; Lethal effect; Cellulose; Polymers; Silver nanoparticle; kovové nanočástice; Spectrophotometry, Ultraviolet; Animals; Metal Nanoparticles; X-Ray Diffraction; biokompatibilní materiály; polymery; Chitin; Microscopy, Electron, Transmission; zvířata; American cockroach; Insecticides; Industrial Microbiology; stříbro; Biocompatible Materials; transmisní elektronová mikroskopie; spektrofotometrie ultrafialová